Morfometria do relevo na bacia do rio da cachoeira no contexto do plano de manejo da floresta nacional de Passa Quatro (MG) - Marques Neto, Roberto [UNESP]; Da Gonçalves, Fábio Silva; Da Conceição, Ramiris Moraes; Da Fernandes, Fábio Silva; Vieira, José Ricardo Machado; Simas, Nemo Gomes (My University, 2008)
The Units of Conservation have a fundamental paper in the process of environmental protection and conservation of the natural resources. In the context of management plan of Units of Conservation, the forms and morphometric patterns of the relief and geomorphological process have got great importance by the fact that they form the physical substratum on wich develop the human activities, answering the alterations provoked by such activities. The analysis of relief is one of the some forms of if understanding the spatial dynamics. In this way, the geomorphological cartography comes as a vital instrument for a appropriate plan. This article shows morphometric aspects of the relief (declivity, vertical dissection and horizontal dissection) in the basin of the Rio da Cachoeira (Waterfall River), area of the Floresta Nacional de Passa Quatro (MG), south of Minas Gerais state, as subsidy to the management plan of the Unity of Conservation and the integrated management of the area.
Relief morphometry in the Cachoeira river basin in the management plan of Floresta Nacional de Passa Quatro (MG)
Keywords: Erosive dynamics; Horizontal dissection; Management plan; Vertical dissection